The Gravity Model of Trade between Czech Republic and Russia - Malkova, Anna; Algozhina, Aliya; Semenenko, Vadim; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This thesis is aimed at constructing the gravity model of trade that examines bilateral trade between the Czech Republic and Russia over twenty-five years period from Q1 1995 to Q1 2020. The purpose of this thesis is to identify important factors that influences trade between two countries and to test if bilateral trade between the Czech Republic and Russia is significant. Thesis is divided into three main chapters. The first chapter touches on theoretical foundation of the gravity model of trade. The second chapter is aimed at constructing and analyzing the gravity model itself. The third chapter presents the economic profile, bilateral trade, as well as economic relations between the two countries. Its purpose is to describe bilateral and economic overview of the Czech Republic and Russia.
Vedoucí práce: Aliya Algozhina
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses